β2 Adrenoceptor Signaling-induced Muscle Hypertrophy from Blood Flow Restriction: Is There Evidence? - Loenneke, J. P.; Wilson, J. M.; Thiebaud, R. S.; Abe, T.; Lowery, R. P.; Bemben, M. G. (Hormone and Metabolic Research, 2012)
Skeletal muscle hypertrophy and increases in muscular function have been observed following low intensity/load exercise with blood flow restriction (BFR). The mechanisms behind these effects are largely unknown, but have been hypothesized to include a metabolic accumulation induced increase in muscle activation, elevations in growth hormone, and improvements in muscle protein balance. However, many of the aforementioned mechanisms are not present with BFR in the absence of exercise. In these situations, signaling through the β2 adrenoceptor has been hypothesized to possibly contribute to the positive muscle adaptions, possibly in concert with muscle cell swelling. Signaling through the β2 adrenoceptor has been shown to stimulate both muscle protein synthesis and an inhibition of protein degradation through increasing cyclic adenosine monophosphate (cAMP) or signaling via the Gβγ subunit, especially in situations where the basal rates of protein synthesis are already reduced. Every study that has investigated the catecholamine response to BFR in the absence of exercise or in combination with exercise has shown a significant increase above resting conditions. However, from the available evidence, it is unlikely that the norepinephrine response from BFR, particularly with exercise, is playing a prominent role with muscle adaptation in skeletal muscle that is not immobilized by a cast or joint injury.
Keywords: catecholamines; norepinephrine; epinephrine